Significance of Manager of Manager toolset in IT Service Management chain: Analysing a resilient IT-OT integration and its impact on IT Visibility within the Mining and Consumer sector - Sharma, Nikhil (Digital Repository of Theses - SSBM Geneva, 2025)
The IT Service Management chain underlined the significance of Manager of Manager toolset provides IT-OT flexibility, especially in the mining industry, which experienced highly convergence impacts due to combination of IT-OT technology. This work aims to explore the effectiveness of different IT Service Management tools and platform approaches used during and after the IT-OT integration to increase mining resilience. To this end, the study extends a wide-ranging literature review to identify how several elements, including digital technology applications, risk management, and mining chain flexibility, have been used to manage disruption and sustain business operations. The study also examines the relationship between resilience and operational performance which encompasses smart causal analysis solution that analyses historical data using specialized correlation and clustering techniques to detect patterns and pinpoint common sources of performance problems. By doing so, the research outlines factors that enhance mining chain resiliency and provides guidance to provides a systematic approach to diagnosing and resolving IT issues, ensuring that technology supports business goals effectively around the globe. The outcomes proved to be quite helpful in understanding these strategies and indicated the increasing need for a strategic approach to IT Service management in mining chain to maintain high performance over time, given the current global context. Furthermore, the research aims to analysing the impact of mining chain resilience on operational performance, focusing on identifying the most critical issues first, enabling the engineers to focus on resolving the most impactful problems, such as ERP connectors and open-source file systems, leading to a significant reduction in incidents and improved service uptime. This research provides guidelines that mining firms can use to strengthen their IT Service Management tool chain and prepare for potential enhancing user experience and improving platform stability by evaluating the effectiveness of the above listed strategies. It also gives an understanding of the main characteristics of mining chain for strength and the essential drivers that foster such strength. The research offers important insights into the suitability of these strategies and underscores the importance of addressing impact of IT-OT convergence risks before they materialize and of maintaining superior performance in a world that increasingly poses consolidation. Keywords: Mining Chain Resilience, IT-OT, Mining Sector, Mining Chain Strategies, Operational Performance, Smart Causal Analysis, Digital Technology Integration, Risk Management, Service Management.